Global DNA hypomethylation is associated with high serum-persistent organic pollutants in Greenlandic Inuit - J. A. Rusiecki; L. E. Moore; E. C. Bonefeld Jorgensen; A. Baccarelli; V. Bollati; L. Tarantini (Environmental Health Perspectives, 2008)
Background: Persistent organic pollutants (POPs) may influence epigenetic mechanisms; therefore, they could affect chromosomal stability and gene expression. DNA methylation, an epigenetic mechanism, has been associated with cancer initiation and progression. Greenlandic Inuit have some of the highest reported POP levels worldwide. Objective: Our aim in this study was to evaluate the relationship between plasma POPs concentrations and global DNA methylation (percent 5-methylcytosine) in DNA extracted from blood samples from 70 Greenlandic Inuit. Blood samples were collected under the Arctic Monitoring and Assessment Program and previously analyzed for a battery of POPs. Methods: We used pyrosequencing to estimate global DNA methylation via Alu and LINE-1 assays of bisulfite-treated DNA. We investigated correlations between plasma POP concentrations and global DNA methylation via correlation coefficients and linear regression analyses. Results: We found inverse correlations between percents methylcytosine and many of the POP concentrations measured. Linear regressions, adjusting for age and cigarette smoking, showed statistically significant inverse linear relationships mainly for the Alu assay for p,p'-DDT (1,1,1-trichloro-2,2-bis(p-chlorophenyl)ethane; β = -0.26), p,p'-DDE [1,1-dichloro-2,2-bis(p-chlorophenyl) ethylene; β = -0.38], β-hexachlorocyclohexane (β = -0.48), oxychlordane (β = -0.32), α-chlordane (β = -0.75), mirex (β = -0.27), sum of polychlorinated biphenyls (β = -0.56), and sum of all POPs (β = -0.48). Linear regressions for the LINE-1 assay showed β estimates of similar magnitudes to those using the Alu assay, however, none was statistically significant. Conclusions: This is the first study to investigate environmental exposure to POPs and DNA methylation levels in a human population. Global methylation levels were inversely associated with blood plasma levels for several POPs and merit further investigation.